2008
DOI: 10.1242/jeb.023101
|View full text |Cite
|
Sign up to set email alerts
|

Timing of the daily temperature cycle affects the critical arousal temperature and energy expenditure of lesser long-eared bats

Abstract: SUMMARYDaily patterns of body temperature (T b ) and energy expenditure in heterothermic endotherms are affected by changes in ambient temperature (T a ) and selection of suitable microclimates, yet most laboratory studies employ constant T a to measure metabolic rates. In particular, exposure to a daily temperature cycle, even within rest shelters, may be important in timing of torpor and arousal and determining resting energy costs in wild animals. We tested how captive bats (Nyctophilus geoffroyi; 7 g) expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 46 publications
5
30
0
Order By: Relevance
“…In nature, grey mouse lemurs reach body temperatures as low as 11.3±1.8°C for an ambient temperature of 9.4°C (Schmid, 2000). Also, in the field, arousal should be helped by rising ambient temperature during the day, with a passive rewarming of torpid animals (Turbill et al, 2008;Schmid, 2000). Such energetic benefits driven by ambient temperature variations were prevented in our experimental design.…”
Section: Discussionmentioning
confidence: 98%
“…In nature, grey mouse lemurs reach body temperatures as low as 11.3±1.8°C for an ambient temperature of 9.4°C (Schmid, 2000). Also, in the field, arousal should be helped by rising ambient temperature during the day, with a passive rewarming of torpid animals (Turbill et al, 2008;Schmid, 2000). Such energetic benefits driven by ambient temperature variations were prevented in our experimental design.…”
Section: Discussionmentioning
confidence: 98%
“…dusk), which suggests that the time of day affects the response of torpid bats to noise disturbance. In general, small nocturnal mammals, including many bat species, exhibit a strong propensity for torpor in the early morning, when daily T a is lowest (Körtner and Geiser, 2000;Turbill et al, 2008). Moreover, torpid animals become more sensitive to a variety of external stimulations as the bout of torpor progresses (Lyman et al, 1982).…”
Section: Torpid Bats and Noise Disturbancementioning
confidence: 99%
“…As a result, tests conducted in the morning are more likely to occur in the early phases of torpor, when torpid animals are generally less sensitive to disturbances (Kristoffersson and Soivio, 1964;Twente and Twente, 1968). Turbill et al (Turbill et al, 2008) have provided clear evidence that the time of day affects the critical arousal temperature of torpid bats. The critical arousal temperature was lower when external heating occurred later in the day.…”
Section: Torpid Bats and Noise Disturbancementioning
confidence: 99%
“…However, only arousals that were closer to midday coincided with a second arousal of nest mates, whereas the rewarming of a group member in the early morning did not obviously affect the T b of other animals. As many species arouse from torpor around midday, synchronized arousals might not be caused by disturbance but by circadian rhythms (Heller and Ruby, 2004;Turbill et al, 2008). However, our study also showed that cooling rates were negatively correlated with the number of warm, normothermic individuals in the group and that TBDs were shorter and T b,min higher the more individuals were normothermic.…”
Section: Discussionmentioning
confidence: 43%